Hydrophobic carbon dots with blue dispersed emission and red aggregation-induced emission - Haiyao Yang (Nature Portfolio, 2019)
Carbon dots that display long-wavelength and multicolor emission are desirable for biological and anti-counterfeiting applications. Here, the authors design hydrophobic carbon dots with reversible two-mode fluorescence, which exhibit blue emission when dissolved in solution, and red solid-state fluorescence when aggregated.